Experiment results of failure progression from low power wires - Samie, Mohammad; Alghassi, Alireza; Jennions, Ian K. (Elsevier, 2017)
Despite various studies that have been conducted so far on the failure of high power cables, failure progression in low power cables, wires and interconnections have not been well understood yet. In general, it is hypothesised that failures of wires are progressed from random intermittent failures that are gradually developed as hard faults. This paper aims to present a test rig and possible test techniques that can be used for testing the failure progression of wires and interconnections. Research presented in this paper is based on tools, equipment and techniques that facilitate various ageing mechanisms needed to capture proper and right failure patterns from low power cables, wires and interconnections. Paper originally presented at the 5th International Conference in Through-life Engineering Services Cranfield University, 1st and 2nd November 2016.
Keywords: No-Fault-Found; Intermittent Fault; Reliability; Accelerated Aging Mechanisms